Pemahaman Konseptual Siswa Kelas VII dalam Menyelesaikan Soal SPLDV Menggunakan Metode Grafik - Feri Prastyo; Annafi Awantagusnik (JURNAL ARMADA PENDIDIKAN, 2024)
Conceptual understanding is something that person has to be able to learn material or to solve problems. One of the mathematical materials related to conceptual understanding is Systems of Linear Equations in Two Variables (SPLDV). The graphic method is a method that is rarely taught by teachers and used by students in solving SPLDV. In fact, by using this method, a person's conceptual understanding can be easily seen and is able to develop students' mathematical representation abilities. This research is a qualitative research to describe the conceptual understanding of class VII SMP students in solving SPLDV questions using the graphic method. The research subjects in this study were three students consisting of students with high, low and medium abilities. Students are given two questions related to SPLDV. Based on the results of the students' work, the researcher carried out data analysis consisting of data reduction, data display, and conclusion drawing. The results of the research show that students' conceptual understanding in solving SPLDV questions using the graphic method is still very low. This is shown by the subject's indicators of conceptual understanding. Of the three indicators of conceptual understanding, both subjects could only meet one indicator and one subject did not even meet any of the indicators. Further research related to increasing conceptual understanding in solving SPLDV questions, especially using graphic methods, needs to be carried out.